The Efficacy and Safety of Rapamycin in Children with Tuberous Sclerosis: A Cross-sectional Study: Efficacy of Rapamycin in treatment of Tuberous Sclerosis - Tehrani , Fateme; Khosroshahi , Nahideh; Keihanidoust , Zarrin; Dabiran, Soheila; Zarkesh, Mohammad Reza (Iranian Journal of Child Neurology, 2023)
Objectives Mutations in TSC1 or TSC2 genes have been proposed as the main causative factors responsible for developingTuberous Sclerosis Complex (TSC). Given the effect of these two genes on the mTOR pathway,rapamycin hasemerged as a novel therapeutic agent.The present study evaluated the effectiveness and safety of rapamycin on the multiple manifestations of TSC. Materials & Methods Twenty-three eligible children were enrolled in the present crosssectional study. They were prescribed rapamycin1mg tablet twice daily for the first two weeks of treatment and then once daily for at least one year.Periodicevaluations through follow-up visits were performed Besides, growth and developmental statuses wereevaluated. All data, including the number and size of brain tuberomas, size of renal angiomyolipomas, and skinlesions, were gathered and recorded, and then analyzed. Results During the study period, the mean number of epileptic episodes significantly reduced (p<0.0001), and nine cases were seizure-free at the final visit. The mean number of brain tuberomas decreased from 19.3±11.0 at the initial visit to 11.1±5.6 and 8.2±3.2 in the subsequent visits (p<0.001). The mean size of brain tuberomas similarly decreased from 17.9±18.5 cm at enrollment to 13.7±5.1 cm and 6.9±5.1 cm in the second and third visits, respectively (p=0.029). The mean size of renal angiomyolipomas significantly decreased (p<0.001). A significant trend toward a decrease in the number of skin lesions was observed (p<0.0001). No relationship was observed between the effects of rapamycin and the patient’s age or sex (p>0.05). Changes in patients’ growth and developmental features were not statistically significant through subsequent visits (p=0.507). Conclusion This study revealed the effectiveness and safety of rapamycin on TSC among our patients